Molecular Identification of Members of Campylobacteriaceae Family in Gallstone - Sheykh Zahed, Neda; Ghane, Masood (Archives of Advances in Biosciences, 2018)
Introduction: The role of Bacterial infections as one major cause of occurrence of gallstones has been admitted. Campylobacteraceae family consists of Helicobacter, Campylobacter and Arcobacter genus have been identified as significant bacteria in the appearance of gastric disorders. This study aimed to investigate the frequency of Campylobacteriaceae family bacteria in the gallstones of patients hospitalized in the surgery ward of Shahid Rajaei hospital in Tonekabon. Materials and Methods: Sample of gallbladder stone was collected form 36 patients. After culture in the BHI medium for the primary enrichment, DNA extraction was carried out and then, the presence of the desired bacteria was examined by PCR technique. The obtained data was analyzed by SPSS software (21) and Chi-square (x2) test. Results: Of total 36 samples of the studied gallstone, 3 samples (8.33%) were positive from viewpoint of presence of Helicobacter, 5 samples (13.88%) were positive in terms of presence of Campylobacter and only 1 sample (2.77%) was positive with respect to the presence of Arcobacter. No significant relationship was observed between type of stone and presence of these bacteria. Conclusion: The results achieved from this research show the presence of DNA belonging to the Campylobacteraceae family in the gallbladder stone, using PCR technique. These bacteria have an etiological significance in the formation of the gallstones. Therefore, more studies are required to determine the role of these bacteria in the formation of gallbladder stone.